(3eHGOF GdEbJUGO GdLRFj (B/s - (3YHO GdQMje, MSf Jhajbs ((3YeGf(B: s (3OGQ UaGA(B, s, 2005)
(3GdeTcdI GdEbJUGOjI hGdeaGgje GdeJYdbI HgG(B-(3Yde GdEbJUGO hCfhGYg(B- (3fXQjI GdbjeI hGdWdH Ydi GdSdY hGdNOeGJ(B- (3GdYQV ef GdSdY hGdNOeGJ(B- (3JaGYd bhj GdWdH hGdYQV aj GdShb(B- (3GdeQhfGJ(B- (3Sdhc GdeSJgdc(B- (3GdEfJGL hGdJcGdja(B- (3JhGRf GdeDSSI aj Xd GdCShGb GdeNJdaI(B- (3CShGb YfGUQ GdEfJGLs
Keywords: (3GdCShGbs; (3GdEbJUGOs; (3GdEfJGLs; (3GdJcGdjas; (3GdWdH hGdYQVs; (3Sdhc GdeSJgdcs